Home-based circuit training program for an adolescent female with severe traumatic brain injury: A case report. (1st February 2018) - Tiwari, Devashish; Daly, Carol; Alsalaheen, Bara
ABSTRACT: Adolescents with traumatic brain injury (TBI) are often discharged from physical therapy (PT) services without transitioning into exertional conditioning programs. Active participation in physical activities with peers at school is essential to achieve a sense of accomplishment and acceptance. Factors such as reduced aerobic fitness and residual gait impairments can lead to limited participation and peer interaction. The purpose of this case report was to describe the impact of home-based circuit training (HBCT) focusing on strength and balance on gait speed (GS), energy expenditure, and functional performance in a 17-year-old female with severe TBI. The participant sustained a TBI from a motor vehicle crash. Although she was ambulatory and independent with the basic activities of daily living following two years of rehabilitation, she presented with activity limitations and participation restrictions at school. The participant performed a 4-week HBCT program developed by a school physical therapist that focused on strength and balance. At the end of 4 weeks, improvements were observed in 6 MWT (change = 79.7 m), GS (change = 0.22 m/s), and the COPM scores (performance score change = 2.8, satisfaction score change = 2.2, MCID = 2). Improvements in functional performance, gait speed, and self-perception of occupational performance were observed following 4-week HBCT. Future clinical trials on short duration, HBCT program for children and young adults with TBI are recommended in order to establish effectiveness of HBCT.